A dual-emissive fluorescent sensor fabricated by encapsulating quantum dots and carbon dots into metal–organic frameworks for the ratiometric detection of Cu2+ in tap water. Issue 33 (14th August 2017) - Ma, Yujie; Xu, Guanhong; Wei, Fangdi; Cen, Yao; Ma, Yunsu; Song, Yueyue; Xu, Xiaoman; Shi, Menglan; Muhammad, Sohail; Hu, Qin
Abstract : A new ratiometric fluorescent sensor (QDs/CDs@ZIF-8) combining the advantages of ratiometry and MOFs was synthesized for Cu 2+ detection. Abstract : A novel ratiometric fluorescent (RF) sensor was synthesized via a facile one-pot route by encapsulating quantum dots (QDs) and carbon dots (CDs) having good fluorescence properties into a zeolitic imidazolate framework (ZIF-8, one of the classical metal–organic frameworks). The as-synthesized QDs/CDs@ZIF-8 composite not only possessed the advantages of a RF sensor, but also accumulated target analytes strongly due to the adsorption ability of MOFs. The composite showed good stability and dispersibility in aqueous solution and was further applied to the detection of Cu 2+ ions. The QDs/CDs@ZIF-8 composite that is used as a RF sensor exhibited excellent sensitivity and selectivity toward Cu 2+ . The linear range was 5–100 nM and the LOD was 1.53 nM (3 σ /K). The QDs/CDs@ZIF-8 composite could be simply used for detecting Cu 2+ in tap water.